Note on logarithmic transformation of the RAS - Henry, EW (Economic & Social Studies, 1973)
The apparently new Least-Squares (LS) minimisation method of R. C . Geary could be applied to the logarithms of the Xij, if the required numerical data were available.
Keywords: RAS